Analisis Kinerja Bongkar Muat Moda Transportasi Barang pada Kawasan Pergudangan - Kasmaida; Hakzah; Rahmat Hidayat; Yusril Fiba (Institut Teknologi Garut, 2026)
Transportation and logistics are strategic aspects in goods distribution, where loading and unloading activities in warehouse areas are key factors determining operational efficiency. Parepare City, as a regional logistics hub in South Sulawesi, still faces challenges such as limited facilities and long truck waiting times due to ineffective loading and unloading scheduling. This study aims to analyze warehouse characteristics, transportation modes, and measure the influence of the quantity of goods (X1), equipment and labor performance (X2), and loading and unloading time (X3) on productivity and effectiveness (Y). The method used is a descriptive quantitative approach through field observations, questionnaires, and documentation studies, with multiple linear regression analysis using SPSS version 27. The study covered six warehouses, consisting of three commercial warehouses, a steel material warehouse using forklifts, a fertilizer warehouse, and a rice warehouse using manual labor. The results show performance disparities, where the steel material warehouse using forklifts recorded the highest productivity of 51 pieces/minute with an R² value of 79.5 percent, while the rice warehouse only reached 8 sacks/minute. Simultaneous (F) and partial (t) tests confirmed that X1, X2, and X3 significantly influence Y. These findings emphasize that optimizing forklift utilization, improving labor competency, and improving loading and unloading scheduling are key factors in increasing logistics efficiency in the Parepare warehouse area.